Review of Infections With Bovine Herpesvirus 1 in Slovenia - Hostnik, Peter; Černe, Danijela; Mrkun, Janko; Starič, Jože; Toplak, Ivan (Frontiers in Veterinary Science, 2021)
In the 1950s, infectious bovine rhinotracheitis/infectious pustular vulvovaginitis (IBR/IPV) was clinically detected and documented in cattle for the first time in Slovenia. It was confirmed and isolated using cell cultures. Bulls in Slovenian insemination centres (IC) have been negative for IBR /IPV infection since 1975. To keep the IC free from the virus, high biosecurity measures were introduced. Before entering the IC, all calves are serologically tested and quarantined. The ICs in Slovenia are IBR/IPV-free, and all bulls are regularly tested for IBR/IPV antibodies. From 1985 to 1991, few large-scale studies of the prevalence of IBR/IPV were carried out. In 1985, a high percentage (56.97%) of serologically positive animals were found in large state farms with Holstein Friesian cattle. Epidemiological studies were also carried out in the farms with Simmental and Brown cows. Antibodies against BoHV-1 were detected in the serum of 2.34% of Brown cattle and 3.46 % of Simmental cattle. In the year 2000, 3.36% of bulk milk samples from 13,349 dairy farms were tested positive. The highest percentage of positive breeding was found in regions with an intensive grazing system (6.22% positive) and the lowest percentage in the east part of Slovenia (0.91% positive) on farms with mostly Simmental cattle. In 2006, sera from cattle older than 24 months were tested for the presence of antibodies to IBR/IPV. Positive cattle were detected in 1,287 (3.57%) farms. These farms kept 34,537 animals that were potential carriers of the IBR/IPV virus. Most of the positive farms kept Holstein Friesian cattle, descendants from the state-owned farms, which were privatised or closed after 1990. In 2015, the Administration of the Republic of Slovenia for Food Safety, Veterinary and Plant Protection issued a rule that describes the conditions for granting and maintaining the status of IBR/IPV-free farms. The rule provides a voluntary control programme for breeders who want to obtain IBR/IPV-free status and are willing to cover all the cost of acquiring and maintaining that status. There has been very little response from breeders.